RESEARCH ON ANTONOMASIA IN THE WORKS OF WILLIAM SHAKESPEARE - Mustafoyeva Nodira Erkin qizi; Achilova Risolat Azamovna (Western European Studies, 2025)
This article discusses the occurrence of antonomasia in English literature, primarily in the works of William Shakespeare, and the extensive use of antonomasia for characters in his writings. Additionally, it addresses the role of antonomasia in Shakespeare's works and their functions.
Keywords: antonomasia; characters